Impact of pumpkin rootstock on DNA methylation and epigenetic profile of grafted self-bred cucumber progeny (Bangladesh Journal of Botany, 2025)
To study the effect of pumpkin rootstock on the variation of self-bred progeny of grafted cucumber, "Zhenghuang 1409" was used as scion, and "Liangzhen No.1" pumpkin was used as rootstock. The alterations in genome DNA methylation of self-bred progeny of grafted cucumber were examined utilizing MSAP technology with the differential bands subsequently  cloned and sequenced. The results showed that the methylation levels of two types of mutant materials in the first and second generations of grafted cucumber inbred lines increased compared to cucumber scion inbred lines, but the methylation levels of single-chain extracellular cytosine or double chain intracellular cytosine in the mutant materials showed almost opposite changes from the first generation (G1) to the second generation (G2) compared to cucumber scion inbred lines; The methylation status of variant types shows opposite changes from G1 to G2. In G1, the degree of methylation of variant type I is greater than the degree of demethylation, while in G2, the degree of demethylation of variant type I is greater than the degree of methylation. The degree of demethylation of variant type II in G1 is greater than that of methylation, while in G2, the degree of methylation of variant type II is greater than that of demethylation. Gene sequence homology analysis of specific fragments of MSAP found that the homologous genes mainly correspond to proteins containing specific domains, enzyme proteins, and carrier proteins, etc. These functional proteins are involved in post-transcriptional regulation, cellular amino acid synthesis, redox, and other processes, etc. The specific fragment of MSAP indicates that the methylation status of its homologous gene is mutated, which may affect the functional expression of its homologous gene, which may affect the growth and development process of the self-bred progeny of grafted cucumber and even affect the phenotypic traits.Bangladesh J. Bot. 54(2): 377-387, 2025 (June)